Relative Humidity of 40% Inhibiting the Increase of Pulse Rate, Body Temperature, and Blood Lactic Acid During Exercise - Sandi, N.; Adiputra, N.; Pangkahila, A.; Adiatmika, P. G. (BALI MEDICAL JOURNAL, 2016)
Background: Excessive sweating of the body is a reaction to decrease the heat caused by prolonged exercise at high relative humidity (RH). This situation may cause an increase in pulse rate (PR), body temperature (BT), and blood lactic acid (BLA) workout. Objective: This study aimed to prove that a RH of 40% better than a RH of 50% and 60% RH in inhibiting the increase of PR, BT, and BLA during exercise. Methods: The study was conducted on 54 samples randomly selected from the IKIP PGRI Bali students. The samples were divided into three groups, and each group was given cycling exercise with a load of 80 Watt for 2 x 30 minutes with rest between sets for five minutes. Group-1 of cycling at 40% of RH, Group-2 at a RH of 50%, and the Group-3 at a RH of 60%. Data PR, BT, and BLA taken before and during exercise. The mean difference between groups before and during exercise were analyzed by One-way Anova and a further test used Least Significant Difference (LSD). Significance used was ? = 0.05. Results: The mean of PR during exercise was significantly different between groups with p = 0.045, the mean of BT during exercises was significantly different between groups with p = 0.006, and the mean of BLA during exercises was significantly different between groups with p = 0.005 (p